UJI SKRINING ASTO (ANTI STREPTOLISIN O) PADA MANUSIA USIA LANJUT (MANULA) DI PANTI SOSIAL TRESNA WERDHA MINAULA RANOMEETO SULAWESI TENGGARA - Susanti Susanti; Angriani Fusvita; Wa Fifi (Program Study of Medical Laboratory Technology , Politeknik Bina Husada Kendari, 2022)
Elderly human is a process of growth that is carried out by every human being, which is characterized by a decrease in the body’s ability to adapt to the environment. Elderly human experience a decline in the immune system so that they are susceptible to various disease. Anti Streptolisin O (ASTO) are antibodies to the resulting streptolysin O antigen by bacterium Streptococcus B hemolyticus group A. Examination of Anti Streptolysin O (ASTO) is a blood test that works for to know the antibodies to streptolysin O produced by Streptolysin group A. The purpose of this study is to know the screening test of result anti streptolisin O (ASTO) in elderly human at the Tresna Werdha Minaula Ranomeeto social institution in Southeast Sulawesi,Elderly human samples were 30 samples with the taking technique sample is total sampling with latex test method. Based on the research that has been done can that from 30 samples there were 4 people (13%) positive samples Anti Streptolysin O (ASTO) is characterized by agglutination and 26 (87%) of the anticipated negative streptolysin O (ASTO) negative samples with no agglutination occuring. Key words: Anti Streptolysin O, Agglutination, Elderly Human, Social Institution